Midaesin - a histone H2A antimicrobial peptide from the South African abalone, Haliotis midae - French, Lee (Department of Molecular and Cell Biology, 2022)
The South African abalone, Haliotis midae, is a commercially important shellfish that is farmed in the Western Cape. Histone H2A-derived peptides investigated from various organisms have been shown to act as antimicrobial peptides (AMPs) against a range of microbes. Therefore, the aim of the study was to determine whether the H. midae histone H2A acts as an AMP and thus plays a role in the innate immune system of this abalone. A peptide fragment corresponding to the first 42 amino acids of the N-terminus of histone H2A was examined in silico. This 4.63 kDa peptide, referred to as Midaesin, was found to possess a high proportion of hydrophobic and basic residues. Secondary structure prediction of Midaesin revealed the presence of an amphipathic α-helix. Alignment of the Midaesin peptide to other known histone H2A-derived AMPs revealed significant sequence similarity. Additionally, RT-qPCR of total cDNA isolated from cultured H. midae haemocytes exposed to heat-killed V. anguillarum for 1h showed that the histone H2A transcript was upregulated, implying a role in the immune response. A PCR-amplified DNA fragment coding for the Midaesin peptide was cloned into a bacterial expression vector and purified. Midaesin-containing peptides inhibited the growth of Staphylococcus aureus, Escherichia coli and Vibrio anguillarum at 10 µM in liquid growth inhibition assays. Scanning electron microscopy and fluorescent microscopy, employing the membrane impermeable dye propidium iodide, revealed membrane disruption of V. anguillarum cells exposed to 13 µM or 30 µM of the Midaesin-containing peptides for 30 minutes, respectively. Secondary structure analysis by circular dichroism indicated a shift in the secondary structure of the Midaesin-containing peptide upon incubation with V. anguillarum cells for 30 minutes with a trend towards more α-helical content. Taken together, the above indicates that histone H2A may be involved in the immune response of H. midae and that Midaesin has the potential to act as an AMP.